2017
DOI: 10.1016/j.brat.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

One or many? Which and how many parenting variables should be targeted in interventions to reduce children's externalizing behavior?

Abstract: This research compared the efficacy of two parenting interventions that vary according to the number and the nature of variables in reducing preschoolers' externalizing behavior (EB). The goal was to identify which parenting intervention format (one-variable versus two-variable) caused higher behavioral adjustment in children. The first was a one-variable intervention manipulating parental self-efficacy beliefs. The second was a two-variable intervention manipulating both parents' self-efficacy beliefs and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Behaviorist theorists believe that changing the parents’ perception of their children is key to changing the child’s behavior. However, other researchers found that instead of the child’s behavior modifying, the parents became conditioned to report the child’s observed behavior with a more positive view (Loop et al , 2017). Consistent with our findings, caregivers of ABA-exposed children reported higher satisfaction ratings with longer intervention exposure, even though their PTSS severity scores did not change significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviorist theorists believe that changing the parents’ perception of their children is key to changing the child’s behavior. However, other researchers found that instead of the child’s behavior modifying, the parents became conditioned to report the child’s observed behavior with a more positive view (Loop et al , 2017). Consistent with our findings, caregivers of ABA-exposed children reported higher satisfaction ratings with longer intervention exposure, even though their PTSS severity scores did not change significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Such programs “focus on helping parents to model more effective behaviour” and produce a statistically significant reduction in child conduct problems (Furlong et al , 2010, p. 3). A large proportion of parenting interventions directly derived from the social learning theory contribute to reduce preschoolers’ externalizing behavior, “but their multimodal format prevents us to know what causes change in children’s behavioral adjustment” (Loop et al , 2017). While researchers are interested in parent involvement in minimizing negative childhood behavior, few studies investigate the extent to which the manipulation of parenting variables influences the caregiver.…”
Section: Discussionmentioning
confidence: 99%